Definitive weekly hypofractionated radiotherapy in cutaneous squamous cell carcinoma: response rates and outcomes in elderly patients unfit for surgery. (24th November 2021) - De Felice, Francesca; Musio, Daniela; De Falco, Dario; Grapulin, Lavinia; Magnante, Anna Lisa; Caiazzo, Rossella; Bulzonetti, Nadia; Tombolini, Vincenzo
Abstract: Introduction: The optimal definitive radiotherapy (RT) scheme in cutaneous squamous cell carcinoma (cSCC) remains controversial, especially in elderly patients. Methods: Data of elderly patients with cSCC lesion(s) treated with weekly hypofractionated RT (8 Gy per week per 7‐8 weeks) were analyzed. Results: Eighteen patients (median age 89 years) with 23 cSCC lesions have been identified including nine males (50%) and nine females (50%). The most common tumor localization was the head and neck region ( n  = 21; 91.3%), and the majority of lesions ( n  = 15; 65.2%) was stage ≥ III. At diagnosis, pain and bleeding were ascribed in 13 (56.5%) and eight (34.8%) cSCC, respectively. Compliance with weekly hypofractionated RT was excellent. The overall response rate at 12 weeks after treatment was 95.7%. Bleeding and pain relief were achieved in all cases. Severe toxicity was not recorded. The 1‐year overall survival was 66.0%. The 1‐year progression‐free survival was 58.7%. Conclusions: Weekly hypofractionated RT provides a safe, efficient, and cost‐effective treatment in elderly cSCC patients with minimal side effects.